Development and the environmental politics unmasked - Shepherd, Christopher (Christopher John), author.
1 online resource (xvii, 281 pages)
Keywords: "Focusing on rural development and environmental conservation, this book brings together the detailed history of development in East Timor under two colonial regimes and under the contemporary conditions of national independence. It focuses on two comparative areas of development and conservation: the politics of development across the three political regimes, and development in independent East Timor across four case studies of interventions delivered by various national or international development agencies. Employing a unique classificatory framework for kinds of approaches to development--coercive orders, mandated orders, negotiated orders--the book looks at the plantation-centred development of Portuguese Timor as a European colony and the integration-oriented development of 'Timor Timur' as Indonesia's 27th province. It examines the neoliberal 'democratic' development of East Timor (or Timor-Leste) in the current context of state and nation-building, before drawing on case studies to examine how development proceeds as a negotiation between the authoritative yearnings of state, non-state and international development actors and the needs of local people to adapt intervention to suit their lived realities"--